Influence of physical activity on students’ physical selfconcept and satisfaction with life: Physical and nonphysical education students’ perspective - Masoumeh Golsanamlou; Vali Mehdınezhad (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to find out the physical and non-physical education students' physical self-concept and satisfaction with life. 470 students were selected randomly as two sample groups (physical and non-physical education students). The valid sample of study was 449. The two questionnaires employed here were the Physical Self-Description Questionnaire (PSDQ-S) and the Satisfaction with Life Scale. SPSS 20 was used to produce the Mean; Standard Deviations; Pearson's Product Moment Correlation (r); One-Sample and Independent t-test; and One-Way Analysis of Variance. The results showed that there was significance difference between non-physical and physical education students about physical self-concept in overall and nine dimensions, except factors of coordination and sport. Physical education students have a positive understanding of their body in comparison with non-physical education students. The results also showed, there was no significance difference between non-physical education and physical education students about satisfaction with life. There was also relatively low positive correlation between physical self-concept in overall and nine dimensions with life satisfaction except factors of body Fat and health. Based on the research findings, it is recommended that universities should pay more attention to physical activity.